Knight's forensic pathology - Saukko, Pekka J.; Knight, Bernard (CRC Press, 2016)
The fourth edition continues to be the definitive international resource for those in training and in practice, covering all aspects of the medico-legal autopsy, including the cause and time of death, interpretation of wounds and every other facet of the investigation of a fatality. The contents are intended to lead the pathologist - and in some countries, the non-pathologist - through the procedures needed in the examination of a body found under obscure, suspicious or even criminal circumstances.